Menginterpretasikan Makna Yang Terkandung Dalam Lagu “Ragu Semesta” Isyana Sarasvati - Aprilia Fuji Lestari; Adrainy P.; Raden Roro Aulia R. (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
This study aims to explore the meaning contained in the song entitled "Ragu Semesta" composed by Isyana Sarasvati from her third album "LEXICON" which was released on November 29, 2019. One of the Indonesian singers, Isyana Sarasvati, born on May 2, 1993. "LEXICON" which is the third album from Isyana Sarasvati attracted attention for showing Isyana's true identity. Isyana's identity is the music that she really liked and admired from a long time ago, classical music. The song "ragu Semester" has varied parts with arrangements with beautiful dynamics and describes the patience of the universe that is never undeniable. The lyrics of the song "Ragu Semesta" are not only related to romance with someone, but it's also about calling yourself a decision-making in life. The methods used to analyze data use a qualitative descriptive method, which is a method that is described by words or sentences separated by categories to obtain conclusions. The expected result of this research is to be able to understand the meaning of describing and expressing the poet's feelings in the reality of life, which cannot escape uncertainty, especially in the search for identity and saturation when undergoing an unhealthy relationship.